8. Neurophysiologic mechanism of neural efficiency in humans: Can it explain performances of athletes and patients with neurodegenerative diseases?. Issue 3 (March 2015) - Babiloni, Claudio; Percio, Claudio Del; Marzano, Nicola; Infarinato, Francesco; Aschieri, Pierluigi; Limatola, Cristina
<x xml:space="preserve">Abstract</x> Problem identification Purpose of our research is the development and testing of procedures for the study of functional brain organization in elite athletes and patients with cerebral neurodegenerative processes to test "neural efficiency" hypothesis (i.e. selective cortical activity in experts). Methodology Cortical activity in elite athletes and patients with Alzheimer's disease (AD) was indexed by the study of electroencephalographic (EEG) oscillations in the resting state condition and during events. Results ATHLETES (Del Percio et al., 2008, 2009, 2010; Babiloni et al., 2009, 2010). More resting state eyes-closed posterior cortical alpha (8–12 Hz) power was observed in elite athletes than in amateur athletes and non-athletes, thus suggesting that athletes' brain is more inhibited in this condition. Furthermore, there was a reduced event-related alpha desynchronization as a sign of less cortical activation in elite athletes than in amateur athletes and non-athletes, during both cognitive and motor events, with some exceptions to be better understood. AD PATIENTS (Babiloni et al., 2004, 2007, 2010, 2013). Less resting state eyes-closed posterior cortical alpha (8–10 Hz) power was observed in prodromic and overt AD than in normal elderly subjects, thus suggesting that patients' brain is less inhibited in this condition. Furthermore, there was a reduced event-related alpha desynchronization as a sign of less cortical activation in the former than in the latter ones during eyes opening. Conclusions "Neural efficiency" as a sign of more selectivity and inhibitory capability of brain oscillatory processes may explain at least in part high cognitive-motor performance in athletes and some cognitive-motor abnormalities in AD patients. Keywords EEG; Cognitive-motor processes; Elite athletes